2015
DOI: 10.1039/c4dt02330g
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical redox reactions of Pu(iii) and Pu(iv) in aqueous nitric solutions

Abstract: The behavior of Pu(iv) and Pu(iii) was investigated in aqueous nitric solutions under ultrasound irradiation (Ar, 20 kHz). In the absence of anti-nitrous reagents, ultrasound has no effect on Pu(iv), while Pu(iii) can be rapidly oxidized to Pu(iv) due to the autocatalytic formation of HNO(2) induced by HNO(3) sonolysis. In the presence of anti-nitrous reagents (sulfamic acid or hydrazinium nitrate), Pu(iv) can be sonochemically reduced to Pu(iii). The reduction follows a first order reaction law and leads to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…This observation is in agreement with the literature and results from the reaction of OH Å radicals with nitrate ions and the subsequent hydrolysis of the generated nitrate radical as discussed above (reactions (13) and (14)) [16,17,21] …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This observation is in agreement with the literature and results from the reaction of OH Å radicals with nitrate ions and the subsequent hydrolysis of the generated nitrate radical as discussed above (reactions (13) and (14)) [16,17,21] …”
Section: Resultssupporting
confidence: 92%
“…Several authors have reported higher H 2 O 2 yield for Ar/(20-30 vol.%)O 2 gas mixtures. This was attributed to much more significant generation of both OH Å and HO 2 Å radicals [12,21,22]. According to these observations, one can assume that the sonication of a correctly tuned system combining nitric acid (in the presence of anti-nitrous reagent) and Ar/O 2 atmosphere may enhance H 2 O 2 yields.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…33,34 Recently, it was shown that 20 kHz ultrasound is a promising alternative for the in situ control of the Pu redox state in nitric solutions. 34,35 In heterogeneous systems, cavitation proceeds with the generation of shock waves and microjets which may significantly affect extended surfaces by the fragmentation of particles, erosion of surfaces, increase of mass transfer, and thickening of diffusion layers. 33,36 Significant improvements under ultrasonic treatment were reported for the oxidative dissolution of uranium carbide and metallic plutonium in nitric solutions.…”
Section: Introductionmentioning
confidence: 99%